Analysis of Bank Mandiri's Entrepreneur Expo Program in Encouraging Entrepreneurial Spirit - Farhani, Hilma; Fikriah, H.; Sukamto, Bambang (Westscience Press, 2023)
Micro, Small and Medium Enterprises (MSMEs) play an important role in Indonesia's economic development, especially in West Java Province. Recognizing this important role of MSMEs, Bank Mandiri has introduced the Entrepreneur Expo Program to support and promote entrepreneurship among MSMEs. This study aims to analyze the impact of Bank Mandiri's Entrepreneur Expo Program on the entrepreneurial spirit of MSMEs in West Java. This study uses a mixed-methods research design, consisting of 200 quantitative surveys and qualitative interviews, to collect data from program participants. The findings show that the program has had a positive impact on MSMEs. Networking opportunities, knowledge transfer and increased confidence have empowered the participants, fostering entrepreneurship in the region. Challenges, including sustainability and access to finance, have also been identified. To address these challenges and improve the effectiveness of the program, several recommendations are proposed, such as expanding post-program support, establishing financial partnerships, and adjusting program content. This study contributes to the understanding of entrepreneurship support programs and provides actionable insights for policymakers, financial institutions, and MSME owners, which can ultimately advance the entrepreneurship ecosystem in West Java.